Important Shades in The Meaning of Military Culture – An Etymological Study - Димитров, Кирил (Научни трудове, 2021)
This study aims to outline and critically analyze key shades in the contemporary meaning of the military culture. An etymological study is conducted, based on a literature review of academic publications in the sphere of military culture. Furthermore, text mining was performed in the bodies of deliberately selected publications in order to explore the contemporary tendencies in developing of the professional language in this sphere. An elaborate set of interconnected, rich shades in the meaning of the military culture are identified, based on the reviewed scientific literature, organized and depicted by creating a useful mind-map. On this base an overarching contemporary definition of the aforementioned term is proposed. The identified items from the set of the reviewed scientific publications in this study are discoverable as open access documents on the first ten electronic pages in the academic database of Google Scholar. Seven shades in the meaning of the military culture are identified. The latter and their attributes are logically arranged by means of mind-map. Finally, a new overarching definition of military culture was formulated, considering its simultaneous realizations on different levels, its cultural forms, functions, pursued aims and means of their accomplishment, modernity in its stakeholder management, and its main impacting factor, i.e. the capability to switch between two alternative states of society.
Keywords: Военна култура; Организационна култура; Корпоративна култура; Национална сигурност и война